Modeling seasonal ice and its impact on the thermal regime of a shallow boreal lake using the Canadian small Lake model - Kallel, Habiba; Nadeau, Daniel F.; Bouchard, Benjamin; Thiboult, Antoine; Mackay, Murray D.; Anctil, François (Frontiers in Environmental Science, 2024)
At high latitudes, lake-atmosphere interactions are disrupted for several months of the year by the presence of an ice cover. By isolating the water column from the atmosphere, ice, typically topped by snow, drastically alters albedo, surface roughness, and heat exchanges relative to the open water period, with major climatic, ecological, and hydrological implications. Lake models used to simulate the appearance and disappearance of the ice cover have rarely been validated with detailed in situ observations of snow and ice. In this study, we investigate the ability of the physically-based 1D Canadian Small Lake Model (CSLM) to simulate the freeze-up, icecover growth, and breakup of a small boreal lake. The model, driven offline by local weather observations, is run on Lake Pich é, 0.15 km 2 and 4 m deep (47.32 • N; 71.15 • W) from 25 October 2019 to 20 July 2021, and compared to observations of the temperature profile and ice and snow cover properties. Our results show that the CSLM is able to reproduce the total ice thickness (average error of 15 cm) but not the ice type-specific thickness, underestimating clear ice and overestimating snow ice. CSLM manages to reproduce snow depth (errors less than 10 cm).However, it has an average cold bias of 2 • C and an underestimation of average snow density of 34 kg m -3 . Observed and model freeze-up and break-up dates are very similar, as the model is able to predict the longevity of the ice cover to within two weeks. CSLM successfully reproduces seasonal stratification, the mixed layer depth, and surface water temperatures, while it shows discrepancies in simulating bottom waters especially during the open water period.